2017
DOI: 10.1039/c6cc08891k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of NH-sulfoximines from sulfides by chemoselective one-pot N- and O-transfers

Abstract: Sulfoximines have recently emerged as interesting motifs for both medicinal and synthetic chemists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
134
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(138 citation statements)
references
References 42 publications
1
134
0
3
Order By: Relevance
“…Under standard S ‐alkylation conditions, the reaction of thiophenol ( 7 a ) with commercial 1‐bromo‐3‐chloropropane ( 8 a ) in the presence of triethylamine gave thioether 9 ab in 78 % yield. One‐pot sulfoximine formation with (diacetoxyiodo)benzene and ammonium carbamate in methanol afforded acyclic sulfoximine 10 ab in a clean reaction with no sign of cyclized product 3 ab , as indicated by TLC and UPLC‐MS analysis. However, initial attempts to isolate 10 ab by preparative HPLC resulted in a mixture of acyclic sulfoximine 10 ab and cyclized 3 ab in about 2:1 ratio.…”
Section: Resultsmentioning
confidence: 87%
“…Under standard S ‐alkylation conditions, the reaction of thiophenol ( 7 a ) with commercial 1‐bromo‐3‐chloropropane ( 8 a ) in the presence of triethylamine gave thioether 9 ab in 78 % yield. One‐pot sulfoximine formation with (diacetoxyiodo)benzene and ammonium carbamate in methanol afforded acyclic sulfoximine 10 ab in a clean reaction with no sign of cyclized product 3 ab , as indicated by TLC and UPLC‐MS analysis. However, initial attempts to isolate 10 ab by preparative HPLC resulted in a mixture of acyclic sulfoximine 10 ab and cyclized 3 ab in about 2:1 ratio.…”
Section: Resultsmentioning
confidence: 87%
“…In order to investigate whether replacing the sulfone moiety with a sulfoximine improves the antiplasmodial activity of the thiochroman scaffolds, sulfoximines 6a and 6b were prepared as shown in Scheme 1 using the protocol reported by Zenzola et al [30,31] our previously reported protocol, [32] was oxidized using 1.2 equiv. of oxone ® to afford sulfoxides 8a and 8b as a separable mixture in 1:3 diastereoisomeric ratio, while oxidation with excess oxone ® led to the formation of sulfone 5 in reasonable yields (Scheme 1).…”
Section: Synthesis Of Sulfoximine Analogues Of the Sulfone-derived mentioning
confidence: 99%
“…[14] The NH transfer occurred with sources of ammonia, with ammonium carbamate preferred, in the presence of bis-(acetoxy)iodobenzene as the oxidant. [16][17][18] Herein, we report the development of an ew strategy for the direct synthesis of NH-sulfonimidamides from sulfenamides as simple,r eadily available,a nd previously unexplored substrates.Ahighly selective one-pot NH and O transfer is achieved using operationally simple conditions. [15] We,a nd others, recently reported related conditions for the conversion of sulfides into sulfoximines in ao ne-pot process through ahighly chemoselective NH and Ot ransfer.…”
Section: Introductionmentioning
confidence: 99%